TRANSMISSION OF DATA IN SECURE MANNER WITH DNA SEQUENCE - Paspula, Ravinder; Chiranjeevi, K.; Kumar, S. Laxman (APTIKOM Publisher, 2020)
A new-promising technology called DNA-Cryptography is emerged in the area of DNA- Computing field.DNA useful for store, sending the data and also to perform computation. Even it is under primal level, DNA-Based molecular Cryptography system is shows extremely efficient. This technique offers a unique cipher-text generation process and a new key generation practice. This method used to implement a procedure which includes two stages. First stage generates a session key and encryption key and it uses cipher block chaining mode-CBC, the secrete number(s) and incorporate plain-text M into level-1 cipher-text. The last stage converts the level-1 cipher-text into level-2 cipher-text (s). The level-2 cipher-text is again transformed into human made DNA-sequence (S?) and is given to the receiver along with many other DNA-sequence. By this process it will become a more complicated for un-authorized user to gain original information. The receiver will apply the process to identify the human made DNA sequence with M hidden in it and extract the original message M.